SAT0446 Reference Curves for The Australian/canadian Hand Osteoarthritis Index (AUSCAN) in The General Population. (15th July 2016) - Kroon, F.; Ramiro, S.; Royston, P.; Le Cessie, S.; Rosendaal, F.R.; Kloppenburg, M.
Abstract : Background: Patient-reported outcomes are important to evaluate treatment, but their interpretation depends on the availability of benchmarks. The AUSCAN is a widely used questionnaire evaluating hand pain, stiffness and function. Objectives: To establish population-based reference curves for the AUSCAN, and to investigate factors associated with AUSCAN scores in the general population. Methods: Analyses were performed in a population-based sample, the Netherlands Epidemiology of Obesity study (n=6671, aged 45–65 years). Participants completed questionnaires on demographic and clinical information, including the AUSCAN (range 0–60, higher is worse). Standardised physical examination of the hands was performed. Primary hand osteoarthritis (OA) was defined as fulfilment of the American College of Rheumatology criteria for hand OA without an inflammatory rheumatic disease. "Pre-hand OA" was defined as having hand pain and at least two bony swellings or deformities of distal interphalangeal joints (IPJs), proximal IPJs or first carpometacarpal joints and not having primary hand OA or an inflammatory rheumatic disease. Age- and sex-specific reference curves were developed using quantile regression in conjunction with fractional polynomials. Factors associated with AUSCAN scores were analysed with ordered logistic regression, since AUSCAN data were non-normally distributed and heavily zero-inflated, dividing AUSCAN into three categories (0 vs. 1–5 vs. >5). Analyses are reported as odds ratios (ORs) with 95% confidence intervals (CIs), representing the OR of being in the highest compared to the middle or lowest category for a unit change in the determinant. The final percentile curves were compared to observed AUSCAN scores of individuals with primary hand OA. All analyses were stratified by sex. Results: Median age was 56 years (interquartile range (IQR) 50–61), 56% were women. Primary hand OA was present in 12% of participants. AUSCAN scores were low (median 1, IQR 0–4). Reference curves were higher for women, and moderately increased with age (figure ). Other associated factors (adjusted for age) were not only primary hand OA (OR 13.8 (95% CI 9.3 to 20.5) and 8.4 (6.2 to 11.4) in men and women), but also self-reported inflammatory rheumatic diseases (OR 2.3 (1.4 to 3.6) and 4.5 (2.7 to 7.5)), fibromyalgia (OR 265 (32 to 2203) and 20.2 (9.6 to 42.5)), "pre-hand OA" (OR 9.8 (6.1 to 15.8) and 5.7 (3.8 to 8.5)), education (as proxy for socio-economic status, OR 0.8 (0.6 to 0.9) and 0.8 (0.7 to 1.0)), and BMI (OR 1.03 (1.00 to 1.06) and 1.03 (1.02 to 1.05)). Median AUSCAN scores of individuals with primary hand OA spread constantly between the 75th and 95th centiles of the general population (figure ). Conclusions: AUSCAN scores in a population-based sample were overall low, and higher in women than in men. These reference curves could serve as benchmark in both research and clinical practice settings in hand OA, although it should be kept in mind that the AUSCAN does not seem to measure hand complaints specific for hand OA. Disclosure of Interest: None declared